The implementation of Post-release Detention Measures for Prisoners According to Section 28 of the Preventive Measures of Recidivism in Sexual or Violent Offenses Act, B.E.2565 (2022) - Trathong, Somprasong (Law for Development Graduate Journal, 2025)
The existing legal framework in Thailand has been deemed insufficient in addressing the risks posed by first-time offenders and recidivists in sexual and violent offenses. The enactment of the Measures for the Prevention of Repeat Offenses in Sexual or Violent Crimes Act B.E. 2565 (2022) aims to mitigate recidivism risks and enhance public safety. However, an analysis of Section 28, which authorizes post-sentence detention of convicted offenders, reveals legal concerns regarding its impact on fundamental rights and freedoms. The study identifies two primary legal issues: (1) the restriction of liberty through post-sentence detention, which extends beyond the originally imposed criminal penalty, and (2) potential conflicts with the principle that an individual shall not be punished multiple times for the same offense. The UN Human Rights Committee’s General Comment No. 35, Paragraph 21, states that if a detention period follows a criminal sentence for public protection purposes, it must be justified by the gravity of the crime and the likelihood of reoffending, and it must be used as a last resort. Furthermore, such detention must be distinct from punitive imprisonment, and any additional restrictions beyond the original sentence must comply with Articles 9 and 15 of the ICCPR, which prohibit retroactive penalties. In response, this study proposes legislative amendments to balance offender rights with public safety: (1) revising the definition of “detention” to align with Section 34, (2) renaming Chapter 5 from “post-release detention measures” to “post-release detention measures for safety,” and (3) adding a new paragraph to Section 28 to exclude cases where the offender has fully served the sentence imposed by the court to prevent multiple punishments for the same offense.